2014
DOI: 10.1159/000365975
|View full text |Cite
|
Sign up to set email alerts
|

Role of the rs6923761 Gene Variant in Glucagon-Like Peptide 1 Receptor Gene on Cardiovascular Risk Factors and Weight Loss after Biliopancreatic Diversion Surgery

Abstract: Background: Studies of the glucagon-like peptide 1 (GLP-1) receptor (GLP-1R) have been directed at identifying polymorphisms in the GLP-1R gene that may be a contributing factor in the pathogenesis of obesity. Objective: We decided to investigate the role of the rs6923761 GLP-1R polymorphism on outcomes after biliopancreatic diversion. Design: A sample of 137 morbidly obese patients was operated. Weight, blood pressure, basal glucose and lipid profile were measured at the basal visit and at each following visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 18 publications
(23 reference statements)
1
18
0
3
Order By: Relevance
“…Tokuyama et al [24] studied 9 types of polymorphisms in GLP-1 R and there were no significant differences in anthropometric parameters. This association has been described by our group [14][15][16][17][18][19][20][21][22][23][24][25]. The mechanism by which GLP-1R variants influence obesity is unclear and potential effects on adipogenesis could be implied.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Tokuyama et al [24] studied 9 types of polymorphisms in GLP-1 R and there were no significant differences in anthropometric parameters. This association has been described by our group [14][15][16][17][18][19][20][21][22][23][24][25]. The mechanism by which GLP-1R variants influence obesity is unclear and potential effects on adipogenesis could be implied.…”
Section: Discussionsupporting
confidence: 58%
“…Finally, the amount of weight loss could be involved, too [14]. For example after bariatric surgery, a study [21] showed a higher weight loss 12 and 18 months after bariatric surgery in GG variant than A allele carriers.…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphic allele was nominally associated with decreased beta cell response [13]. In addition, the association between rs6923761 and basal GLP-1 levels in naïve patients with diabetes mellitus type 2 was observed [32], and the contributing role of rs6923761 in weight loss after bilio-pancreatic diversion was investigated [14]. In our pilot study, carriers of at least one polymorphic rs6923761 A allele tended to have better treatment response compared to carriers of two wild type G alleles.…”
Section: Discussionmentioning
confidence: 78%
“…There is some data that single nucleotide polymorphisms (SNPs) which result in substitution of certain amino acids may alter binding affinity for GLP-1 and intracellular signaling after hormone-receptor binding [13]. The aim of the study was to assess the association of common non-synonymous GLP-1R SNPs rs6923761 and rs10305420, selected based on data from SNP database or previously published studies [13][14][15], with weight loss in response to liraglutide in obese women with PCOS. The GLP-1R SNP rs6923761 was previously associated with pathogenesis of obesity [14], whereas clinical implications of rs10305420 have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The SNP rs6923761 (Gly168Ser) was nominally associated with reduced insulin secretion in response to GLP‐1 infusion during a hyperglycemic clamp in nondiabetic American subjects and with a weaker response to the glucose‐lowering effect of DPP‐4 inhibitors in patients with T2DM . On the contrary, the same polymorphism was associated with higher efficacy of liraglutide, and it was shown to increase weight and fat mass loss after liraglutide treatment, different types of diet, or bilio‐pancreatic diversion surgery . In addition, carriers of the rs6923761 A allele had higher basal GLP‐1 levels and a better cardio‐metabolic profile .…”
Section: Summary Of the Literaturementioning
confidence: 99%